The Correlation Between Students’ Vocabulary Achievement and Fluency in Speaking English - Dwhy Dinda Sari (English Teaching and Linguistics Journal (ETLiJ), 2021)
The objective of the study was to find out the correlation between students vocabulary achievement. The population was the second grade student of SMK Negeri Binaan PEMPROVSU. The population were 5 class consist 121 students. This study took a class TKJ and TKR as a sample by using Cluster Random Sampling. In gathering data, used a match test to measure vocabulary mastery and oral test to measure fluency in speaking English. In analyzing data, this study used Pearson Product Moment Formula. After analyzing, it was found r- calculated 0,873. It means that r-calculated was higher than r- table. So the relationship between two variables above were significant. And percentage if correlation between students’ vocabulary achievement and fluency in speaking English was 76,22%. It means that the students’ vocabulary achievement will support fluency in speaking English